High accumulation of microplastic fibers in fish hindgut induces an enhancement of triphenyl phosphate hydroxylation. (15th January 2023) - Chen, Qiqing; Gao, Zhuo; Wang, Kang; Magnuson, Jason T.; Chen, Yuye; Li, Mingyuan; Shi, Huahong; Xu, Li
Abstract: Fiber shedding from artificial textiles is among the primary sources of pervasive microplastics in various aquatic habitats. To avoid molten drop burning, triphenyl phosphate (TPhP), a typical flame retardant additive, is commonly incorporated into textile fibers. However, the role of microplastic fibers (MFs) as a vehicle for TPhP remains largely unknown. In this study, we investigated the effects of MFs on the bioaccumulation and metabolism of TPhP in zebrafish. We applied the compound spinning technique for a non-disruptive in situ measurement of fluorescent MFs in fish, and the desorption electrospray ionization mass spectrometry (DESI-MS) to display the tissue distribution of TPhP and its metabolites vividly. Laboratory results showed that ingested MFs did not change the TPhP distribution in fish; however, they statistically increased the metabolite p -OH-TPhP concentration in the fish hindgut, which was probably because the high accumulation of MFs there enhanced the TPhP hydroxylation. Field investigation further supported the lab-based analyses. Higher concentrations of MFs did cause a higher ratio of [ p -OH-TPhP]/[TPhP] in the wild fish gut, particularly in the hindgut. Collectively, our results demonstrated that MFs can change the distribution and bioavailability of TPhP metabolites, which was confirmed by both laboratory and fieldwork. Therefore, the ingestion of MFs can indirectly but substantially influence the bioaccumulation and biotransformation of co-existing pollutants. Graphical abstract: Image 1 Highlights: Microplastic fibers (MFs) in the fish gut enhanced the hydroxylation of TPhP. The MFs ingestion did not change the accumulation of parent TPhP in fish. Desorption electrospray ionization mass spectrometry (DESI-MS) is a powerful MS imaging method. Various amounts of MFs were detected in wild fish collected from different rivers. Field work confirmed MFs' effects on the accumulation and metabolism of TPhP.